Paradigm of Virtue in Sharia Economics in Surah Al-Imran Verse 92 - M Yosi Ramadan; Muhibban; Ahmad Farishin Ikhwan (Penerbit Hellow Pustaka, 2024)
The blessing paradigm is an important concept in sharia economics which emphasizes the importance of blessings in economic activities. This research aims to examine the virtue paradigm in sharia economics based on Surah Al-Imran verse 92. This verse is believed to provide a strong foundation for the importance of giving and donating property on the path of Allat SWT. This study uses the tafsir analysis method to understand the meaning and content of the verse related to virtue in sharia economics. It is hoped that the results of this study can contribute to the development of sharia economic discourse that is oriented towards virtue and prosperity.